Sistem Informasi Pengajuan Perizinan berbasis WEB di SD Negeri 2 Bloro - Santoso, Firman; Rizqiana, Rizqiana; Nisyak, Helyatin; Fitriyah, Nadzirotul (Fakultas Sains dan Teknologi, Universitas Ibrahimy, 2024)
In today's internet-based era, web-based technology has been widely used to assist system processing in a company or institution. One of them is in the process of applying for a permit, where the system currently running at SD Negeri 2 Bloro still uses the conventional model, namely with written media. The purpose of this research is to build a website-based licensing application information system application which makes it easier for educators to apply for permits. This study uses the waterfall method in designing a web-based licensing information system at SD Negeri 2 Bloro, where the process is carried out in stages. Starting from the analysis, design, implementation, testing and maintenance. Data collection techniques through interviews, observation and documentation. PHP is a web-based programming language that is server-side, which means that the PHP programming code is processed entirely on the web server. MySQL is a language that has good enough capabilities to support the work of developers. In this study, building a website-based employee licensing application at SD Negeri 2 Bloro uses the PHP programming language and MySQL database. The application is planned in the form of a website so that permit applications are dynamic, practical, and can be accessed anywhere, anytime, and by all educators.